4-H Senegal Community of Practice Developing STEM Curricula that Leads to Youth-driven Discovery and Innovation - Fatima Z Kebe; Hannah H Scherer (Journal of International Agricultural and Extension Education, 2023)
In 2015, Jeunesse en Agriculture (JEA), French for “Youth in Agriculture” formed 4-H clubs in Senegal, West Africa. JEA set out to develop culturally relevant STEM curricula for their 4-H youth learners. This led to the novel formation of the 4-H Senegal STEM Community of Practice (CoP), a group designed to create engaging content and activities that leverage local interest and resources. The CoP Practice used a conceptual framework that applies the United States National Research Council’s Engage-Respond-Connect framing as criteria contextualized for 4-H Senegal STEM learning. JEA team members and the CoP used a design-based educational research approach to developing and testing new STEM curricula. The STEM curricula use the Do- Reflect- Apply model for learning through experience, along with scientific inquiry and engineering design as methodologies for youth learners to investigate and develop solutions on topics of their interest. This research note describes 4-H Senegal’s development of meaningful STEM content that enables youth-driven discovery and innovation.
Keywords: 4-H; STEM; Community of Practice; Experiential Learning; Youth-Driven; Scientific Inquiry; Engineering Design